THE EFFECT OF TEACHER-STUDENT INTERACTION AND FRIENDSHIP QUALITY ON ACADEMIC MOTIVATION OF MODERN ISLAMIC BOARDING SCHOOL FEMALE STUDENTS AFTER DISTANCE LEARNING: Pengaruh Interaksi Guru-Siswa Dan Kualitas Pertemanan Terhadap Motivasi Akademik Siswi Pesantren Modern Pasca Pembelajaran Jarak Jauh - Thoyyibah, Kalimah; Alfiasari (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
Distance Learning (PJJ) has been ongoing for the past two years due to the Covid-19 pandemic. As the pandemic subsided, the government decided to resume face-to-face learning in the classroom. For pesantren that have not conducted face-to-face learning for a long time, this condition requires new adaptations, especially in reviving students' academic motivation. This study aims to analyze the effect of teacher-student interaction and friendship quality on the academic motivation of modern pesantren students after PJJ. This study involved 112 modern pesantren student respondents and was conducted with an explanatory study design. Data collection was self-administered at school through questionnaires distributed directly in class. Data analysis was carried out descriptively and inferentially, including correlation tests and multiple linear regression tests. The correlation test results showed that adolescents' education level was significantly negatively related to teacher-student interaction. Family income is significantly positively related to friendship quality. Length of stay in pesantren has a significant negative effect on academic motivation. The results of the effect test show that the length of stay in pesantren, teacher-student interaction, and friendship quality have a significant positive effect on the academic motivation of modern pesantren students after PJJ.